Encyclopedia of Individual Work-Related Personality Traits, Attitudes, and Behaviors: Understanding People at Workplace - Dr. Noor Un Nisa; Dr. Muhammad Nawaz Baloch (Encyclopedia of Individual Work-Related Personality Traits, Attitudes, and Behaviors: Understanding People at Workplace, Edition 1, 2024)
This book is comprised of three major elements associated with an individual’s personality, which include Traits, Attitudes and Behaviours. More specifically author tried to address these elements under the work-related domain. However, due to the identical and interrelated nature of elements related to personality traits, attitude and behaviour author could not categorize each element under a distinct label. In this book, the authors tried to define most of the personality traits, attitudes and behaviour related to work with the help of internet sources, literature and authors’ understanding. This book works as an encyclopedia to search different personality traits, attitudes and behaviours and will be useful and helpful for new researchers to identify them and explore them further.